Skills, personality traits, and gender wage gaps: Evidence from Bangladesh - Christophe J. Nordman; Leopold R. Sarr; Smriti Sharma (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We use a recent first-hand linked employer-employee survey covering the formal sector of Bangladesh to explain gender wage gaps by the inclusion of measures of cognitive attainment and personality traits. Our results show that cognitive skills have greater explanatory power than personality traits in determining mean wages. Unconditional quantile regressions show that cognitive attainment as measured by reading and numeracy seems to confer different benefits on women and men respectively. The Big Five trait of agreeableness is positively associated with females' wages across the wage distribution. Decompositions show that about 30-40 per cent of the wage gap can be explained by characteristics along the wage distribution. Cognitive skills cumulatively account for a larger share of the explained component than personality traits do, and matter more at lower percentiles. However, together these cognitive and socio-emotional skills matter to a lesser degree than factors such as one's tenure in the firm.
Keywords: J16; J24; J31; J71; C21; O12; 330; Gender wage gap; cognitive skills; personality traits; matched worker-firm data; Bangladesh